Early adolescent levels of self-regulation of online gaming in SMP YAPPA Depok: Analysis of Rasch modeling - Tanti Ardianti; Lucky Riandika Marfu'i; Fijriani Fijriani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The study aims to uncover and analyze how big is the level of self-regulation of early adolescent students towards online gaming addiction behavior at Yappa Junior High School Depok. The method used in this research is quantitative with a descriptive survey analysis approach regarding the ability of students to manage themselves against online game addiction. This research variable is a single variable, namely self-regulation of online games which is an independent variable (X). This self-regulation analysis is expected to be owned by every student so that they are able to control themselves in playing online games both at home or at school. The results found that the level of early adolescent self-regulation of online games is quite good.